Modified Frailty as a Novel Factor in Predicting the Maintenance of the Sinus Rhythm After Electrical Cardioversion of Atrial Fibrillation in the Elderly Population - Mlynarska A (Dove Medical Press, 2020)
Agnieszka Mlynarska,1,2 Rafal Mlynarski,2,3 Czeslaw Marcisz,1 Krzysztof S Golba2,3 1Department of Gerontology and Geriatric Nursing, School of Health Sciences, Medical University of Silesia, Katowice, Poland; 2Department of Electrocardiology, Upper Silesian Heart Centre, Katowice, Poland; 3Department of Electrocardiology and Heart Failure, School of Health Sciences, Medical University of Silesia, Katowice, PolandCorrespondence: Agnieszka MlynarskaDepartment of Gerontology and Geriatric Nursing, Upper-Silesian Medical Centre, ul. Ziolowa 45/47, Katowice 40-635, PolandFax +48 32 2524098Email mlynarska83@gmail.comIntroduction: Frailty is a common geriatric syndrome that causes an elevated risk of catastrophic declines in the health and function among older adults – we hypothesized that frailty may be related to the maintenance of sinus rhythm after cardioversion.Methods: The study sample was a group of 199 consecutive patients over 60 (average age 71.41 ± 6.99; 40.2% women) with AF who were hospitalized in order to perform electrical cardioversion. The Tilburg Frailty Indicator (TFI) was used to assess frailty before cardioversion. The six-month visit after the electrical cardioversion was a follow-up. The follow-up period for the maintenance of sinus rhythm after electrical cardioversion was 180 ± 14 days.Results: Patients in whom cardioversion was effective had a statistically significantly lower severity of frailty syndrome (3.44 ± 1.83 vs 5.87 ± 1.12; p=0.000) and its components: physical components (2.14 ± 1.33 vs 3.62 ± 1.05 p=0.000); emotional components (0.92 ± 0.79 vs 1.29 ± 0.86 p=0.037) and social components (0.37 ± 0.56 vs 0.96 ± 0.46; p=0.000) compared to those patients in which cardioversion was ineffective. In the logistic regression, frailty (OR: 0.65, 95% CI:0.5010– 0.8330; p=0.000) was observed to be an independent predictor for maintaining sinus rhythm.Conclusion: Frailty is a novel, independent factor that can be used to predict the effectiveness of electrical cardioversion and the maintenance of sinus rhythm in the elderly population. Modifying the level of recognition in the Tilburg Frailty Indicator to a 4 improved the prediction of the effectiveness of electrical cardioversion as well as the maintenance of sinus rhythm.Keywords: frailty, atrial fibrillation, electrical cardioversion, sinus rhythm